2020
DOI: 10.1002/acn3.51121
|View full text |Cite
|
Sign up to set email alerts
|

Consistent improvement with eculizumab across muscle groups in myasthenia gravis

Abstract: Objective To assess whether eculizumab, a terminal complement inhibitor, improves patient‐ and physician‐reported outcomes (evaluated using the myasthenia gravis activities of daily living profile and the quantitative myasthenia gravis scale, respectively) in patients with refractory anti‐acetylcholine receptor antibody‐positive generalized myasthenia gravis across four domains, representing ocular, bulbar, respiratory, and limb/gross motor muscle groups. Methods Patients with refractory anti‐acetylcholine rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Eculizumab inhibits C5 cleavage into C5a and C5b, hence blocking MAC formation. The drug resulted in the clinical benefit of refractory AChR-positive gMG patients in the phase III REGAIN trial, and the following open-label extension study, demonstrating that eculizumab is able to elicit a rapid and sustained improvement in muscle strength [ 19 , 20 , 21 , 22 ]. Zilucoplan, a small macrocyclic peptide that allosterically inhibits C5 cleavage, also generated meaningful improvement in patients with moderate to severe gMG in the phase III RAISE study ( ; , accessed on 8 April 2022), strengthening the evidence of complement inhibition efficacy in gMG [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eculizumab inhibits C5 cleavage into C5a and C5b, hence blocking MAC formation. The drug resulted in the clinical benefit of refractory AChR-positive gMG patients in the phase III REGAIN trial, and the following open-label extension study, demonstrating that eculizumab is able to elicit a rapid and sustained improvement in muscle strength [ 19 , 20 , 21 , 22 ]. Zilucoplan, a small macrocyclic peptide that allosterically inhibits C5 cleavage, also generated meaningful improvement in patients with moderate to severe gMG in the phase III RAISE study ( ; , accessed on 8 April 2022), strengthening the evidence of complement inhibition efficacy in gMG [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The viability of this approach has been demonstrated by studies providing evidence that eculizumab improves clinical outcomes in adult patients with anti-AChR antibody-positive refractory gMG and is well-tolerated (9)(10)(11)(12), which led to its approval in the USA (adults with AChR antibodypositive gMG), Canada (adults with AChR antibody-positive treatment-refractory gMG), Europe (adults with AChR antibodypositive treatment-refractory gMG), and Japan (patients with AChR antibody-positive gMG whose symptoms are difficult to control with high-dose intravenous immunoglobulin therapy or plasmapheresis) (13)(14)(15)(16)). In the 6-month, double-blind, placebo-controlled, Phase 3 REGAIN study, clinically meaningful improvements in activities of daily living, muscle strength, functional ability, and health-related quality of life were observed in patients with gMG who received eculizumab (10,12,(17)(18)(19). These clinical improvements were sustained through 3 years of continuous treatment in the open-label extension phase of this study; patients in the open-label extension who had previously received placebo in the REGAIN study also demonstrated a rapid response to eculizumab (11,12,(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…In the 6-month, double-blind, placebo-controlled, Phase 3 REGAIN study, clinically meaningful improvements in activities of daily living, muscle strength, functional ability, and health-related quality of life were observed in patients with gMG who received eculizumab (10,12,(17)(18)(19). These clinical improvements were sustained through 3 years of continuous treatment in the open-label extension phase of this study; patients in the open-label extension who had previously received placebo in the REGAIN study also demonstrated a rapid response to eculizumab (11,12,(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Among the changes of QMG scores, eculizumab and efgartigimod were superior to placebo and eculizumab was superior to rozanolixizumab, but there was no statistically significant difference between the remaining drugs which is same as the previous studys. ( Farmakidis et al, 2018 ; Mantegazza et al, 2020 ). The effectiveness of each of the four drugs was compared, but it was not evident which drug was most effective in treating MG. We therefore calculated the SUCRA values for each drug and ranked them accordingly.…”
Section: Discussionmentioning
confidence: 99%